Regioselective palladium-catalyzed ring-opening reactions of C1-substituted oxabicyclo[2,2,1]hepta-2,5-diene-2,3-dicarboxylates - Edmunds, Michael; Raheem, Mohammed Abdul; Boutin, Rebecca; Tait, Katrina; Tam, William (Beilstein Journal of Organic Chemistry, 2016)
Palladium-catalyzed ring-opening reactions of C1 substituted 7-oxanorbornadiene derivatives with aryl iodides were investigated. The optimal conditions for this reaction were found to be PdCl2(PPh3)2, ZnCl2, Et3N and Zn in THF. Both steric and electronic factors played a role in the outcome of the reaction as increasing the steric bulk on the bridgehead carbon decreased the yield. These reactions were found to be highly regioselective, giving only one of the two possible regioisomers in all cases. A diverse collection of novel, highly substituted biphenyl derivatives were obtained.
Keywords: aryl iodides; oxabenzonorbornadiene; palladium catalysis; regioselectivity; ring-opening reactions